A theory of evidence based on audit assertions - SMIELIAUSKAS, WALLY; SMITH, LLOYD (Contemporary Accounting Research, 1990)
This paper refines a theory of audit evidence in light of recent research in philosophy of science. We improve the definition of confirming evidence and relate it to various audit opinions. Specifically, we identify explanations as a critical component linking evidence to audit assertions. An implication of our work is that professional audit standards setting should put increasing emphasis on the explanations underlying audit assessments. Résumé. Les auteurs perfectionnent une théorie relative à l'information probante à la lumière des travaux de recherche récents en philosophie de la science. Ils raffinent la définition de preuve de corroboration et la relient à diverses opinions du vérificateur. De façon précise, ils traitent les explications comme un élément critique reliant l'information probante aux assertions auxquelles s'intéresse le vérificateur. Leurs travaux les mènent entre autres à la conclusion que les normes professionnelles de vérification devraient accorder une place de plus en plus grande aux explications sous‐jacentes à ces assertions.